KEEFEKTIFAN PENGGUNAAN MEDIA INFOGRAFIS TERHADAP PEMAHAMAN SISWA PADA MATERI SISTEM PERNAPASAN MANUSIA DI SEKOLAH DASAR - Ahmad Rafihudin Rafsanjani; Muslimin Ibrahim; Muhammad Thamrin Hidayat; M. Sukron Djazilan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' low understanding of the human respiratory system is a challenge in elementary science and social studies (IPAS) learning because the material is abstract and difficult to observe directly. This study aimed to determine the effectiveness of infographic media in improving students' understanding of the human respiratory system. A quantitative approach with a pre-experimental one-group pretest-posttest design was employed. The participants were 27 fifth-grade students at SD Iskandar Said Surabaya. Data were collected using learning implementation observation sheets, pretest-posttest questions, and a student response questionnaire. The data were analyzed using percentage and N-Gain analyses. The findings showed that learning implementation reached 100% (very good). The average student score increased from 43.33 on the pretest to 92.59 on the posttest, with an average N-Gain of 0.87 (high). Student responses reached 97.96%, indicating a very positive perception of the media. Therefore, infographic media is effective in improving elementary students' understanding of the human respiratory system.